Digital Interventions for Substance Abuse and Addiction Recovery: A New Frontier in Care - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The landscape of addiction treatment is undergoing a profound transformation, driven by the convergence of digital health technologies and artificial intelli...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics